Magneto-Optical Sensing of the Pressure Driven Magnetic Ground States in Bulk CrSBr - Pawbake, Amit; Pelini, Thomas; Mohelsky, Ivan; Jana, Dipankar; Breslavetz, Ivan; Cho, Chang-Woo; Orlita, Milan; Potemski, Marek; Measson, Marie-Aude; Wilson, Nathan P; Mosina, Kseniia; Soll, Aljoscha; et al. (Nano letters, 2023)
Competition between exchange interactions and magnetocrystalline anisotropy may bring new magnetic states that are of great current interest. An applied hydrostatic pressure can further be used to tune their balance. In this work, we investigate the magnetization process of a biaxial antiferromagnet in an external magnetic field applied along the easy axis. We find that the single metamagnetic transition of the Ising type observed in this material under ambient pressure transforms under hydrostatic pressure into two transitions, a first-order spin-flop transition followed by a second-order transition toward a polarized ferromagnetic state near saturation. This reversible tuning into a new magnetic phase is obtained in layered bulk CrSBr at low temperature by varying the interlayer distance using high hydrostatic pressure, which efficiently acts on the interlayer magnetic exchange and is probed by magneto-optical spectroscopy.
Keywords: extreme conditions; magnetic phase transition; van der Waals materials; magnetic materials; optical spectroscopy